(Analysis of anxiety, depression, and their contributing factors in medical staff during quarantine after completing medical aid work during the COVID-19 epidemic) - Li (Li); Jian (Jian); Bei (Bei); Tifang (Tifang); Yuexiang (Yuexiang); Haihong (Haihong) (中西医结合护理)
(Objective To analyze the anxiety, depression, and their contributing factors in medical staff during quarantine after completing medical aid work during the COVID-19 epidemic. Methods A retrospective review was performed. The mental health status and associated contributing factors of the medical staff were surveyed using the pre-selected questionnaire. The three-part pre-selected questionnaire consisted of general information, the 7-item Generalized Anxiety Disorder (GAD-7) scale, and the 9-item Patient Health Questionnaire (PHQ-9). Results A total of 121 questionnaires were received by the open-electronic-questionnaire platform, and 120 valid questionnaires were finally obtained. The mean GAD-7 score was (3. 58 ± 4. 21) points, and 36 (30. 00%) medical staff had anxiety-related symptoms. The mean PHQ-9 score was (2. 54±3. 59) points, and 29 (24. 17%) medical staff had depression-related symptoms. The presentation of fear of being infected with COVID-19 was the main factor contributing to the occurrence of depression symptoms during quarantine ［OR=0. 32, 95% CI(0. 12, 0. 85), P=0. 023］. Conclusion Fear of being infected with COVID-19 was the main reason for depression. It is of great significance to maintain the mental health of medical staff during quarantine. )